Determinantes - Prata, Gustavo Gomes (2016)
This paper wants to provide subsidies to the Mathematics teacher of Basic Education, regarding to Determinants. From a consistent theoretical basis, it builds the concept of Determinant and deducts its main properties. Subsequently, it presents some of its applications, which can be explored in High School, linked to the historical context in which they were developed, aiming to make learning of Determinants more significant. Thereby, the Chapter 1 presents basic concepts of Linear Algebra, which are prerequisites for the definition and study of the Determinant Function, as well as of its properties, which are developed in Chapter 2. Chapter 3, on the other hand, promotes connections of Determinants with other middle-level mathematical concepts related to the own Linear Algebra and Analytic and Euclidean Geometry, each one with a specific historical introduction.